Causativity And Alternation Me-Kan /-I In Indonesian (e-Journal of Linguistics, 2019)
Language study is a way of expressing various language phenomena based onmacrolinguistics and microlinguistics point of view. The study of macrolinguistic aspects focuseson languages relating to other disciplines. On the contrary, microlinguistic study focuses more onlanguage structures, such as phonology, morphology, syntax, and semantics. In this paper, theanalysis focuses on the aspect of the Indonesian typology phenomenon from the ponit of view ofvalence verb of transitive verb based on verb formation process meng-kan/i. The analysis resultsdescribe that verbs with affix me-i/-kan form causative construction of both formal and semanticparameters; Verb alternation with affix me-i/-kan can be applied when verbal constructionpresents locative and benefactive roles in two different constructions; The alternation occursbecause it is tied to grammatical relation constructing a clause construction; and the alternationof meng/i raises the verb's valence level in the clause construction
Keywords: alternation; formal parameter; valence